PERBEDAAN I’ROB PADA TEKS GHAIRU ULI AL-DHORURI DALAM SURAT AN-NISA (Telaah kitab Ahkamul Qur’an karya Al-Jashash) - Ria Puspitasari (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2022)
The focus of this study is to reveal the differences in the recitation of the verses of the Qur'an contained in QS. An-Nisa' verses 95-96 expressed by Abu Bakr Ahmad Ibn Ali Al-Razi or known as Al-Jashash which is written in his book Ahkam al-Qur'an. The research method used in this study is a literature review, where the author examines and studies literature sources related to this discussion. The results of this study state that these differences in qirra'ah are the impact of the existence of several qira'ahs that are developed and recognized, the differences in qira'ah themselves arise because of the different dialects of Muslims to make it easier for Muslims to read, memorize and understand. Al-Qur'an. Differences in qira'ah sometimes affect the legal basis, sometimes not, this is what causes differences in interpretation among commentators. In al-Jashash's interpretation it is explained that the word can be read as rofa' and also nashab, is read rofa' because it is a na'at from الْقَاعِدُونَ and can be read nashab because it is located as a thing. Lafadh basically denotes the meaning of istisna' which denotes a partial exclusion of the whole.